ECONOMIC TRENDS OF UKRAINE’S DEVELOPMENT AND PRIORITIES OF REALIZATION OF NATIONAL ECONOMY POTENTIAL - MATIUKH, Sergii; LOPATOVSKYI, Victor; KRAVCHYK, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The aim of the article is to analyze the state and trends of Ukraine’s economy at the current stage of its development, as well as to substantiate the strategic priorities of state policy to overcome challenges and ensure better realization of the potential of Ukraine’s national economy. The study reveals the urgency of the problem of forming and effective use of Ukraine’s economic growth potential. The analysis of the structure of the population of Ukraine (by the status of labor force, employed and unemployed) in 2010-2021. The situation regarding wages and arrears of its payment in the types of economic activity of the economy of Ukraine is analyzed. The dynamics of volumes of industrial products sold by domestic enterprises in 2010-2021, including by industries of Ukraine, is reflected. The structure of domestic industrial production as of January 2022 is described. The information on indices of construction products and agriculture, forestry and fisheries in Ukraine in 2015-2021 is given. The analysis of positions of economy of Ukraine in the world rating of digital competitiveness is carried out. The key problematic aspects and obstacles to the realization of Ukraine’s economic potential are summarized, in particular, the deterioration of intellectual and human resources and the growth of the volume and level of unemployment; low level of wages and increase in arrears of wages; irrational structure and small volumes of industrial production; instability of production and sales of products of the real sector of the economy; weak positions of big business entities; low innovation and technological activity and the ability to carry out full-scale digital transformation of the national economy. The applied significance of the research results is that the strategic priorities of the systemic state policy of establishing an effective model of economic growth in Ukraine, namely - the diversification of international economic relations and foreign trade; ensuring the stability and independence of the financial system of the state; convergence of the social security system with leading international practices; realization of the potential of "drivers" of economic sovereignty and development; strengthening energy independence, increasing energy efficiency and savings; building and improving the capacity of critical infrastructure elements; ensuring the functional and structural integration of the economic complex.